2019
DOI: 10.1002/jcp.28184
|View full text |Cite
|
Sign up to set email alerts
|

Tiaopi huxin recipe improved endothelial dysfunction and attenuated atherosclerosis by decreasing the expression of caveolin‐1 in ApoE‐deficient mice

Abstract: The Tiaopi Huxin recipe (TPHXR) is widely used in traditional Chinese medicine for the clinical treatment of coronary heart disease. However, the mechanism of TPHXR treatment of atherosclerosis (AS) has not been fully elucidated. In this study, we have aimed to explore the potential antiatherosclerotic effect of TPHXR and its underlying mechanisms. Male ApoE knockout (ApoE−/−) mice were fed a high‐fat diet for 12 weeks and were randomly divided into four groups: the control group, and the low‐dose, medium‐dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Improving endotheliumdependent vasodilatation and restoring endothelial function in patients with atherosclerosis may prevent cardiovascular events [30]. In addition, preventing impairment of endothelium-dependent relaxation was found to attenuate atherosclerosis in ApoE -/mice [31]. Our results revealed impaired endothelium-dependent vasodilatation induced by ACh in ApoE -/mice fed a western-type diet, suggesting endothelial dysfunction in ApoE -/mice.…”
supporting
confidence: 49%
“…Improving endotheliumdependent vasodilatation and restoring endothelial function in patients with atherosclerosis may prevent cardiovascular events [30]. In addition, preventing impairment of endothelium-dependent relaxation was found to attenuate atherosclerosis in ApoE -/mice [31]. Our results revealed impaired endothelium-dependent vasodilatation induced by ACh in ApoE -/mice fed a western-type diet, suggesting endothelial dysfunction in ApoE -/mice.…”
supporting
confidence: 49%
“…Further, compared to that in ApoE −/− mice, caveolin-1 −/− ApoE −/− mice showed reduced endothelial activation and reduced VCAM-1 expression in the aorta, which was partly due to the disruptions in the transfer and accumulation of LDL in the arterial wall [18]. Moreover, the inhibition of caveolin-1 results in the attenuation of atherosclerotic lesions in ApoE −/− mice, which is associated with decreased NF-kB-mediated inflammation [19]. Furthermore, caveolae have also been reported to regulate ROS production through NADPH oxidase (Nox) by modulating oxidative stress and ox-LDL-induced cellular senescence in the vasculature [4,20].…”
Section: 1mentioning
confidence: 89%
“…Traditional Chinese herbal medicines have been shown to be beneficial for the treatment of cardiovascular diseases by targeting caveolin. The Tiaopi Huxin recipe, a traditional Chinese medicine widely used to treat coronary heart disease, was recently shown to decrease the expression of caveolin-1, thereby improving endothelial function and reducing atheromatous lesions in ApoE −/− mice [19]. Further, Yan et al [89] showed that Zhuanggu Jianxi Decoction, a traditional Chinese medicine, inhibits IL-1β-induced activation of the caveolin-p38MAPK pathway, thereby suppressing the inflammatory response.…”
Section: Therapeutic Promisingmentioning
confidence: 99%
“…The pathogenesis of AS progresses with EC dysfunction [26,27]. It is known that oxidative stress causes endothelial Figure 3.…”
Section: Discussionmentioning
confidence: 99%